Financial Performance Banking Model in Indonesia Before and After Implementation of PBI No. 13/1/PBI/2011: Risk Profile Bank Regional Development - Sintha, L (KnE Social Sciences, 2018)
The study was conducted at the Regional Development Bank, recorded by Bank Indonesia in the period 2008–2014 by taking a sample of 10 banks. Data collection methods used were literature and documentation. Data were analyzed using multiple linear regression analysis test, two different test proportion. This study aimed to examine the effect of differences in the implementation of the norm of Bank Indonesia Number: 13/1/PBI/2011 that took effect from the beginning of 2012 as compared to before the enactment of the regulation. Variable Risk Profile with dimensions of Credit Risk, Market Risk, Liquidity Risk and Operational Risk affected the financial performance of the model as a proxy Earning as interest Net Margin (NIM) and Return On Assets (ROA) in the Regional Development Banks. The data used in this study were obtained from the Quarterly Financial Report issued by the Bank Indonesia. The results showed that there were significant differences in variable interest Risk Profile to Net Margin (NIM) and Return On Assets (ROA) before and after the application of the Regulation of Bank Indonesia in 2011. Keywords: Risk Profile, Credit Risk, Market Risk, Liquidity Risk, Operational Risk